PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDEN, AKTIVITAS KOMITE AUDIT, DAN KEPEMILIKAN MANAJERIAL TERHADAP KECURANGAN LAPORAN KEUANGAN - Tan Novita Angelina; Anis Chariri (Diponegoro Journal of Accounting, 2022)
This study aims to obtain empirical evidence about the effect of corporate governance on financial statements. The corporate governance variables used are the proportion of independent commissioners (COMINDEP), audit committee activity (ACMEET), managerial ownership (OSHIP) with profitability and leverage as control variables. The population of this study are non-financial companies listed on the Indonesia Stock Exchange in 2009 – 2020. The total sample used in this study is 50 companies consisting of 25 companies categorized as companies that report financial statements based on the Otoritas Jasa Keuangan (OJK) report. and 25 companies that do not report financial statements as comparisons selected based on industry and total assets. The data analysis used was descriptive statistical analysis, multicollinearity test, and hypothesis testing through logistic regression using SPSS 26 software. The results of this study indicate that the proportion of independent commissioners (COMINDEP) has a negative and significant effect on financial statements. Meanwhile, audit committee activity (ACMEET) and managerial ownership (OSHIP) have no significant effect on financial statement reporting.